Espaço cultural comunitário do Cacau Pirêra: a promoção da cultura através da arquitetura regional - Fernandes, Gabriela Pinto (Brasil, 2022)
The proposed theme rehearses a project of a Community Cultural Space for Cacau Pirêra, located in the municipality of Iranduba in the state of Amazonas, Northern region of Brazil. Through the proposal, it seeks to discuss the valorization of the Amazonian culture, the adaptation of cultural programs for children, youth and adults focused on rescuing and strengthening their cultural heritage, promotion of diverse activities through multipurpose and specialized spaces, bringing resources and equipment that can contribute to the development of the local community, boosting the development of local sustainable projects and articulating the network of public and social support policies, besides operating as the "heart of collective life" and the main reference element for community life in the district. With the apparatus of studies done about the municipality of Iranduba, the district of Cacau Pirêra and the region that comprises the Amazon, in which a diagnostic study of the territory was developed, where both infra-structural and social and spatial aspects were analyzed, a palafitic architectural proposal arises, which aims not only to resignify the community life, but also to requalify the surroundings in which it is inserted, stimulating the coexistence and the rescue of the visceral relationship that the Amazonian people have with nature and the promotion of community life, through regional architecture.